2015
DOI: 10.1074/jbc.m115.660175
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin D Locates in the Nucleus at Sites of Active Transcription and Modulates Gene and Protein Expression

Abstract: Cystatin D is an inhibitor of lysosomal and secreted cysteine proteases. Strikingly, cystatin D has been found to inhibit proliferation, migration, and invasion of colon carcinoma cells indicating tumor suppressor activity that is unrelated to protease inhibition. Here, we demonstrate that a proportion of cystatin D locates within the cell nucleus at specific transcriptionally active chromatin sites. Consistently, transcriptomic analysis show that cystatin D alters gene expression, including that of genes enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Another three inflammatory markers, consisting of TGF-α, EN-RAGE, and OSM, only correlated with age in the patients and, interestingly, were also increased in the plasma from patients compared to CBD ( Figures 1B and 2B). The strongest correlation with age in CBD was observed for CDCP1, a molecule with a role in immune cell migration and chemotaxis [29][30][31], whereas in the patients, the strongest correlation was observed for CST5, a cysteine protease inhibitor which can also modulate gene transcription and protein expression [32,33]. The inflammatory markers that varied with age can be grouped according to function and are shown in Figure 2C for the two groups.…”
Section: Effects Of Age On Levels Of Inflammatory Markers In Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Another three inflammatory markers, consisting of TGF-α, EN-RAGE, and OSM, only correlated with age in the patients and, interestingly, were also increased in the plasma from patients compared to CBD ( Figures 1B and 2B). The strongest correlation with age in CBD was observed for CDCP1, a molecule with a role in immune cell migration and chemotaxis [29][30][31], whereas in the patients, the strongest correlation was observed for CST5, a cysteine protease inhibitor which can also modulate gene transcription and protein expression [32,33]. The inflammatory markers that varied with age can be grouped according to function and are shown in Figure 2C for the two groups.…”
Section: Effects Of Age On Levels Of Inflammatory Markers In Plasmamentioning
confidence: 99%
“…Our study corroborates that CDCP shows the strongest correlation with age in healthy individuals [59], whereas CST5 (cystatin D) has the strongest correlation with age in the patients. CST5 is an inhibitor of lysosomal and secreted cysteine proteases, but can also locate to the nucleus and modify gene transcription [33]. Interestingly, CST5 is an ultra-early biomarker of traumatic brain injury [32].…”
Section: Inflammatory Markers In Psychiatric Disordersmentioning
confidence: 99%
“…Cystatin D was reported to inhibit proliferation, migration and invasion of carcinoma cells (Alvarez-Díaz et al, 2009 ). In addition, it was shown that a proportion of cystatin D is targeted to cell nucleus at specific transcriptionally active chromatin sites (Ferrer-Mayorga et al, 2015 ). Type-3 cystatins are high molecular weight (60–120 kDa) proteins and have three repeated type 2-like cystatin domains (Salvesen et al, 1986 ).…”
Section: Cystatinsmentioning
confidence: 99%
“…As a suppressor of lysosomal and secreted cysteine proteases, cystatin D (CST5) degrades multiple targets which contain matrix components, adhesion proteins and other proteases. 6 Cystatin D is a member of cystatin family II, which is from the cystatin superfamily. 7 It was demonstrated that CST5 expressed lowly in patients with bladder cancer and human immunodeficiency virus type 1 (HIV-1).…”
mentioning
confidence: 99%